IL-2 Modulates TAMs Derived Exosomal MiRNAs to Ameliorate Hepatocellular Carcinoma Development and Progression. (21st February 2022) - Chen, Hao; Tang, Chao; Tan, Chun; Wu, Fei; Li, Zhenhan; Ji, Wenyan; Lu, Linming; Xu, Chongjun; Shen, Zhengchao; Huang, Yanqiang
Abstract : Background . Interleukin-2 (IL-2) is proved to play an irreplaceable role in antitumor regulation in numerous experimental and clinical trials. Tumor-associated macrophages (TAMs) are able to release exosomes to promote the development and progression of hepatocellular carcinoma (HCC) as essential component of microenvironment. In this study, our intention is to explore the effects of the exosomes from TAMs with IL-2 treatment on HCC development. TAMs were collected and cultured from HCC tissues. The exosomes from the TAMs treated with IL-2 (Exo IL2-TAM ) or not (Exo TAM ) were identified and used to treat HCC cells in vivo and in vitro . The proliferation, apoptosis, and metastasis of HCC cells were measured. The changes of miRNAs in exosomes were explored to clarify the possible mechanisms. Both decrease of cell proliferation and metastasis and increase of apoptosis were observed with Exo IL2-TAM treatment compared with Exo TAM in vivo and in vitro . miR-375 was obviously augmented in Exo IL2-TAM and HCC cells treated with Exo IL2-TAM . Taken together, IL-2 may modulate exosomal miRNAs from TAMs to ameliorate hepatocellular carcinoma development. This study provides a new perspective to explain the mechanism by which IL-2 inhibits hepatocellular carcinoma and implies the potential clinical value of exosomal miRNAs released by TAMs.